2021
DOI: 10.1016/j.jare.2020.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin alleviates acute kidney injury by inhibiting ferroptosis

Abstract: Graphical abstract A proposed model illustrating the therapeutic effect of QCT on AKI. QCT inhibits the expression of ATF3. While ATF3 blocks the system Xc-, and then suppresses GPX4, inducing ferroptosis. In another side, ferroptotic cells secrete chemokines like CCL2, CCL7, induce the recruitment of macrophages, and then cause the inflammation in AKI. In summary, QCT ameliorates AKI through the inhibition on ferroptosis and the following inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
235
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(249 citation statements)
references
References 52 publications
14
235
0
Order By: Relevance
“… 17 The levels of lipid ROS can be determined using BODIPY-C11 dye. 18 , 19 Lipoxygenases (LOXs) may be involved in the formation of iron-dependent lipid ROS by catalysing the oxidation of PUFAs into lipid hydroperoxides and forming toxic lipid-free radicals in the presence of a large number of iron ions in the cytoplasm, which may eventually lead to cell damage. 20 Meanwhile, protons beside PUFAs can be transferred by these toxic lipid-free radicals and then start a new round of lipid oxidation reactions, which eventually lead to more severe oxidative damage.…”
Section: Mechanisms Of Ferroptosismentioning
confidence: 99%
“… 17 The levels of lipid ROS can be determined using BODIPY-C11 dye. 18 , 19 Lipoxygenases (LOXs) may be involved in the formation of iron-dependent lipid ROS by catalysing the oxidation of PUFAs into lipid hydroperoxides and forming toxic lipid-free radicals in the presence of a large number of iron ions in the cytoplasm, which may eventually lead to cell damage. 20 Meanwhile, protons beside PUFAs can be transferred by these toxic lipid-free radicals and then start a new round of lipid oxidation reactions, which eventually lead to more severe oxidative damage.…”
Section: Mechanisms Of Ferroptosismentioning
confidence: 99%
“…Moreover, acute treatment with quercetin before I/R prevented mouse kidney function and limited morphological alterations. In this model, quercetin reduced tubular necrosis, renal inflammation and increased the levels of antioxidant pathways and GSH (190). In addition to its effect on ferroptosis, a plausible explanation for the effects of quercetin is the induction of the antioxidant enzyme HO-1 (191).…”
Section: F) Inhibitors Of Ferroptosismentioning
confidence: 82%
“…Flavonoids form a class of polyphenolic compounds (tannins in the broad sense) ubiquitous in vascular plants (including vegetables and cereals). An in vitro study has shown that quercetin inhibits ferroptosis in renal proximal tubular epithelial cells (190). Moreover, acute treatment with quercetin before I/R prevented mouse kidney function and limited morphological alterations.…”
Section: F) Inhibitors Of Ferroptosismentioning
confidence: 99%
“…In this study, quercetin was the most significant compound, which is closely related to semen quality. Quercetin, a compound belonging to the flavonol class, has extensive pharmacological actions, such as antioxidant and anti-inflammatory effects [ 32 ]. In vitro experiments have shown that adding quercetin to semen can elevate the total antioxidant potential and ameliorate lipid peroxidation during cryopreservation to improve sperm motility, acrosome integrity, plasma membrane integrity, mitochondrial activity and chromatin condensation [ 33 ].…”
Section: Discussionmentioning
confidence: 99%